PENGARUH UPAH MINIMUM PROVINSI, PDRB DAN INVESTASI TERHADAP PENYERAPAN TENAGA KERJA SEKTOR INDUSTRI DI PULAU JAWA TAHUN 2010-2016 - Desy Meilasari (Jurnal Akuntansi AKTIVA, 2020)
This research aims to analyze the effect of provincial Minimum wage (UMP), PDRB, and investment in theindustrial sector of labor absorption on Java island in 2010-2016. Data used is a data panel consisting of datatime series 2010 – 2016 and cross section six provinces namely DKI Jakarta, West Java, Central Java, INYogyakarta, East Java, and Banten. The Anaalisis tool used is a data regression panel i.e. Fixed Effect Model(FEM). The results showed that UMP has a significant effect on the labor absorption of the industrial sector onJava Island in 2010-2016. While the PDRB and investment have a positive and significant effect on the laborabsorption of industrial sectors in Java Island in 2010-2016. Through this research, the government expectsmore cautious and creating a conducive investment climate so that the value of PDRB is increasing.